PRIMARY LARYNGEAL ASPERGILLOSIS IN AN IMMUNOCOMPETENT PATIENT: (case report) - Rajmohan, K.S.; Khan, I. D.; Kapoor, U.; Hashmi, S. A.; Gupta, R. M.; Sen, S.; Nair, G. L.; Singh, K. K.; Tandel, K.; Malik, M. (International Journal of Medicine and Medical Research, 2020)
Background. Aspergillus is an inherently ubiquitous, weakly pathogenic fungus causing opportunistic infections. It is very rarely localized in the larynx, although laryngeal Aspergillosis may develop in the immunocompromised patients including those with leukaemia and severe aplastic anaemia. Objective. The aim of the research was to explore the primary laryngeal Aspergillosis in an immunocompetent patient thru a case report. Methods. A case report of primary laryngeal Aspergillosis in an immunocompetent patient is presented. Results. A male patient of 40 years old, presenting with chronic worsening hoarseness, was found to have a smooth, white spheroid submucosal growth on left vocal cord with preserved bilateral cord movements on videostroboscopy. Histopathological examination of vocal cord growth revealed squamous epithelium containing septate hyphae with acute angle dichotomous branching pattern consistent with Aspergillus. Voice improved after a four-week course of oral itraconazole 200 mg/day. Post therapy follow up of 24 months was unremarkable. Conclusions. Primary laryngeal Aspergillosis develops in the immunocompetent patients. Iatrogenic, vocal abuse, occupation and lifestyle factors may be contributory. Optimal diagnosis and management mandates a high index of suspicion.